Digital Anxiety and Learning Focus Among Senior High School Students: A Mixed-Methods Study from Buddhist Psychology Perspective in Wonogiri, Indonesian - Indi Darma Oktavia; Hesti Sadtyadi; Novianti Novianti; Indi Darma Oktavia; Hesti Sadtyadi (Universitas Negeri Malang, 2026)
This study investigated digital anxiety and its relationship with learning focus among senior high school students in Wonogiri, Indonesia, employing an explanatory sequential mixed-methods design integrated with Buddhist psychological perspectives. The quantitative phase collected data from 40 students using a validated 48-item questionnaire measuring social media use, digital literacy, and digital anxiety, while the qualitative phase conducted in-depth interviews with six purposively selected participants. Quantitative analysis revealed that 95% of students experienced moderate-to-high levels of digital anxiety, with a strong positive correlation between social media use and digital anxiety. Qualitative thematic analysis identified four interconnected themes forming a cyclical pattern: digital distraction patterns, academic guilt and regret, concentration difficulties, and reflective awareness with coping efforts. The integration of quantitative and qualitative findings through joint display analysis demonstrated convergence between statistical relationships and lived experiences, with high social media users reporting more intense distraction patterns and guilt. Cross-tabulation analysis revealed no significant gender differences in anxiety levels, suggesting the phenomenon affects students regardless of gender. The cyclical pattern identified parallels the Buddhist psychological concept of restlessness-worry, providing a culturally relevant framework for understanding digital anxiety among Indonesian adolescents. These findings suggest that comprehensive interventions should address multiple points in the anxiety cycle, combining mindfulness-based approaches with digital literacy education.